Mechanical properties of high performance self-curing concrete using hydrogel polymer diapers - Mohamad D.; Beddu S.; Zahari N.M.; Zawawi M.H.; Syamsir A.; Ismail I.N.; Rasidi D.I.S.; Sapuan W.K.M. (American Institute of Physics Inc., 2023)
High Performance Concrete that can overcome cracking is being research till today. Cracking in High Performance Concrete is the result of poor curing method or procedure. Sometime, the structure characteristic itself becomes a problem for proper curing. One of the method to proper curing method is by using internal curing agent. Hydrogel in baby diapers is used for this internal curing agent. It is mix into the concrete during the casting procedure and the percentage amount of the hydrogel is 0.5%, 1.0%, 1.5% and 2.0%. The concrete with and without hydrogel undergoes slump test, compressive test, split tensile test and water absorption test. The results of the concrete with and without hydrogel are compared. The batch with the maximum compressive strength is the batch with 2.0% of hydrogel while the optimum batch of concrete is the batch with 1.5% of hydrogel. 2018 Author(s).